(untitled) ("Temas Sociais" Journal, 2026)
This exploratory qualitative study examines the influence of poverty on adherence to and retention in continuous HIV care among HIV-positive individuals living in Goba, Namaacha District, Maputo Province, Mozambique, between October 2023 and August 2024. Findings indicate that financial deprivation continues to negatively affect adherence and retention despite the expansion of HIV services, limiting patients’ ability to meet essential clinical and non-clinical needs. The study highlights the importance of integrating state-led basic social protection mechanisms into HIV care services.